Length-length and length-weight relationships of Carcharhinus falciformis and C. signatus (Carcharhinidae: Carcharhinus) caught by commercial fisheries in the Southwest Atlantic Ocean - Domingues, Rodrigo R. [UNESP]; Caltabellotta, Fabio P.; Amorim, Alberto F. (Elsevier, 2016)
Sharks of the genus Carcharhinus are captured as bycatch in longline fisheries and through different fishing gears. Due to the common practice of head and fin removal of sharks, the lack of morphometric data and weight on landings by species hinders the implementation of management measures, since they are needed to perform a stock assessment. Here, we present the length-length (LLR) and length-weight (LWR) relationships of the silky shark (n=145) and night shark (n=90) caught by the commercial pelagic longline fisheries in the Southwest Atlantic Ocean (22°S-33°S; 25°W-50°W) between April 2009 and August 2010. All length-length and length-weight relationships were extremely significant with the coefficient of determination (r2) ranging around 0.99. There were no significant differences in the regression parameters of the length-length and length-weight relationships between males and females to both species. These results represent the first reference on the LLRs and LWRs to silky shark and night shark, using the carcass length (CL - distance between the origin of the pectoral fin to the origin of the caudal fin, in cm) as the basis for all conversion factors.
Keywords: Bycatch; Fisheries management; Morphometric; Night shark; Silky shark